Stronger Syntactic Alignment in the Presence of an Interlocutor - Schoot, Lotte; Hagoort, Peter; Segaert, Katrien (Frontiers in Psychology, 2019)
Speakers are influenced by the linguistic context: hearing one syntactic alternative leads to an increased chance that the speaker will repeat this structure in the subsequent utterance (i.e. syntactic priming, or structural persistence). Top-down influences, such as whether a conversation partner (or, interlocutor) is present, may modulate the degree to which syntactic priming occurs. In the current study, we indeed show that the magnitude of syntactic alignment increases when speakers are interacting with an interlocutor as opposed to doing the experiment alone. The structural persistence effect for passive sentences is stronger in the presence of an interlocutor than when no interlocutor is present (i.e. when the participant is primed by a recording). We did not find evidence however that a speaker's syntactic priming magnitude is influenced by the degree of their conversation partner's priming magnitude. Together, these results support a mediated account of syntactic priming, in which syntactic choices are not only affected by preceding linguistic input, but also by top-down influences, such as the speakers’ communicative intent.